Chemical vapor deposition growth of large single-crystal bernal-stacked bilayer graphene from ethanol. (October 2016) - Chen, Xiao; Xiang, Rong; Zhao, Pei; An, Hua; Inoue, Taiki; Chiashi, Shohei; Maruyama, Shigeo
Abstract: Using ethanol as a precursor, single-crystal bilayer graphene domains with dimensions up to hundreds of micrometer, one of the largest reported so far, were synthesized on Cu foils by chemical vapor deposition (CVD). Raman spectroscopy analysis revealed that the bilayers are homogeneously AB-stacked, with very low D-band intensity. Selected area electron diffraction analysis also confirmed the bernal stacking order and the large area crystallinity. Surprisingly, decreasing ethanol pressure in CVD shows an unambiguous tread from self-limited single layer to a multi-layer graphene, and there exists a narrow window of ethanol pressure which is preferred for the formation of large domain bilayer graphene. This suggests the dual effect of ethanol in graphene growth and demonstrates that the formation of different layers of graphene can be controlled by carefully tuning single parameter: ethanol pressure.